1991
DOI: 10.1111/j.1365-2141.1991.tb08010.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐GPIIb/IIIa (CD41) monoclonal antibody‐induced platelet activation requires Fc receptor‐dependent cell‐cell interaction

Abstract: We studied platelet activation by UR1, a murine IgG1 anti-CD41 mAb. Like thrombin and crosslinked anti-Fc gamma RII mAb IV3, UR1 initiates prompt aggregation and Ca2+ mobilization. UR1 F(ab')2 fragments failed to activate, yet inhibited UR1 IgG-mediated activation. UR1-induced activation was blocked by anti-Fc gamma RII mAb. High viscosity (15% dextran or Ficoll), which impedes cell-cell interaction, inhibited activation by UR1. Cell-cell interaction was confirmed by cell-mixing studies. UR1 binding to platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…First, although neither Mócsai et al 22 nor we (B.B. and P. J. Newman, unpublished observations, January 2008) have been able to coimmunoprecipitate an integrin with an ITAMbearing receptor, evidence that they may be nevertheless topographically associated, at least in platelets, derives from the observations that (1) preincubation of certain ␣IIb␤3-specific antibodies with platelets inhibits the binding of both the anti-Fc␥RIIa mAb, IV.3, and human aggregated IgG, 72 whereas (2) certain other anti␣IIb-␤3 mAbs bind in such a way as to present their Fc regions to Fc␥RIIa, resulting in robust platelet activation [73][74][75][76] -an event that can be totally blocked by preincubation with IV.3. Our observation that IV.3 Fabs prevent ligand binding-induced, ␣IIb␤3-mediated activation of Fc␥RIIa, Syk, and PLC␥2, as well as platelet spreading on immobilized fibrinogen (Figure 1), strongly supports this concept.…”
Section: Outside-inmentioning
confidence: 99%
“…First, although neither Mócsai et al 22 nor we (B.B. and P. J. Newman, unpublished observations, January 2008) have been able to coimmunoprecipitate an integrin with an ITAMbearing receptor, evidence that they may be nevertheless topographically associated, at least in platelets, derives from the observations that (1) preincubation of certain ␣IIb␤3-specific antibodies with platelets inhibits the binding of both the anti-Fc␥RIIa mAb, IV.3, and human aggregated IgG, 72 whereas (2) certain other anti␣IIb-␤3 mAbs bind in such a way as to present their Fc regions to Fc␥RIIa, resulting in robust platelet activation [73][74][75][76] -an event that can be totally blocked by preincubation with IV.3. Our observation that IV.3 Fabs prevent ligand binding-induced, ␣IIb␤3-mediated activation of Fc␥RIIa, Syk, and PLC␥2, as well as platelet spreading on immobilized fibrinogen (Figure 1), strongly supports this concept.…”
Section: Outside-inmentioning
confidence: 99%
“…However, previous work by us and others has demonstrated that the target antigens of several mAb themselves have active signalling roles (Morel et al, 1989;Slupsky et al, 1992;Griffith et al, 1991;Alessio et al, 1993), and that in the generation of an antigenic signal, FcyRII has an anchorage or cross-linker function (Slupsky et al, 1992;Anderson et al, 1991 ;Rubinstein et al, 1991b;Horsewood et al, 1991). Therefore, to avoid signalling associated with FcyRII engagement, it is necessary to block this receptor and to provide an alternative cross-linking of antigen-bound mAb.…”
Section: Resultsmentioning
confidence: 97%
“…These antibodies may trigger platelet activation via platelet FcRs. For instance, GP IIbIIIa-specific monoclonal antibodies have been suggested to activate platelets via the platelet FcγRIIA (Anderson et al, 1991;Rubinstein et al, 1991;Berndt et al, 1993;Deckmyn et al, 1998). Platelet antibodies may also affect the megakaryocytes in the bone marrow.…”
Section: Pathophysiology Of Autoimmune Thrombocytopeniamentioning
confidence: 99%
“…In HIT, a macromolecular complex composed of heparin (or low-molecular-weight-heparin or highly sulphated oligosaccharides) and platelet factor 4 has been demonstrated to serve as an antigen for the immunoglobulin (Greinacher et al, 1994a & b;Amiral et al, 1995). Interactions of the immunoglobulin with the platelet FcγRIIA, by cross-linking of FcγRIIs, will trigger intravascular platelet activation and lead to increased destruction of peripheral platelets (Anderson et al, 1991). Platelet FcR function (Warkentin et al, 1992) and density (Chong et al, 1993) may be correlated with the reactivity of platelets with HIT antibody.…”
Section: Heparin-induced Thrombocytopenia (Hit)mentioning
confidence: 99%